Dvärgmus funnen på Åland 2015 - Stjernberg, Torsten (Memoranda Societatis pro Fauna et Flora Fennica, 2016)
Occurrence of the harvest mouse Micromys minutus confirmed in the Åland IslandsThe harvest mouse, Micromys minutus (Pallas, 1771), is widespread in Finland, except on the Åland Islands, where it has been lacking until now. It has only recently been recorded from the Scandinavian Peninsula, where it first was found in 1985, in Dalsland county in SW Sweden (Loman 1986). Since then, more records have been made in Sweden, both in Dalsland, Värmland, Skåne, Västgötland and also as far north as Norrland (Enoksson 1990, Enoksson & Loman 2004, Hagström 2004, Hallman 2005, Råberg & Holmqvist 2008, Kooij et al. 2016). In Norway the first record was made in 2001, in Hedmark county, SE Norway (Kooij et al. 2001).On 23rd of August 2015 a freshly dead juvenile (5,6 g) harvest mouse was found on the west coast of Enklinge, an inhabited 6 ˟ 3 km island in the NE archipelago of the Åland Islands. The specimen, now in the collection of the Finnish Museum of Natural History, was found 3–4 m from the shore line, in the upper part of a small meadow, below the terrace of a small cottage (all coordinates given in ETRS-TM35FIN, N 6705814 / E 154822). It is supposed to have been caught by a cat, repeatedly seen in the neighbourhood. No catching of micromammals has been conducted on Enklinge. However, on the larger neighbouring inhabited island Kumlinge, ca 5 km S of Enklinge, micromammals systematically were caught in 1984 and 1985, however, with no records of harvest mice.Some observations of harvest mice from islands off the Finnish mainland are also reported. A harvest mouse was caught in the 1970s on the small island Pitkäkari (N 6729971 / E 185887) in the municipality of Kustavi. In June 2013 22 dead harvest mice were found in a washing-up bowl in a small summer cottage on the island Stor-Wehaks (N 6750722 / E 189006) off the city Uusikaupunki, at the west coast of the Bothnian Sea. Records of harvest mice from two islands off Dalsbruk in the municipality of Kimitoön SE from Turku are also reported (Lilla Öland, N 6658925 / E 252374, Träskön, N 6654924 / E 249616). On the south coast of the island Örö (N 6638241 / E 238682), in the outer part of the Archipelago Sea National Park, one harvest mouse was caught in a light trap for Lepidoptera 28.9–7.11.2016. Further east, in the western part of the Gulf of Finland, on the island Gästans (ca N 6645285 / E 317008), in the outer part of the Snappertuna (Raseborg) archipelago, harvest mice and their nests were recorded already in the later part of the 1950s, and again in the early 1980s, at least in 1984. Micromammals have systematically ben caught 1985–2016 in a house inhabited all-the-year-round on the island Sondarö (N 6684027 / E 447912) in the municipality of Pernå. The northernmost part of Sondarö is 0,4 kilometer apart from the mainland. Harvest mice have been caught in the house 1985, 1989, 1995, 2005, 2009 and 2013, out of which 2005 was extraordinary rich in harvest mice.Finally, there is a comment on the water vole (Arvicola terrestris) whose recent and ongoing postglacial expansion to the west has reached the easternmost islands of the Åland Islands, a process documented especially by studying prey remnants in nests of the Eagle Owl (Bubo bubo) on islands and treeless skerries.